Repurposing antiviral drugs targeting the PARP-1 and HER2 pathways with multifaceted impacts through integrated network analysis and molecular mechanics - Uma Maheshwari Mugundan; Praveen Sekar; Rajanandh Muhasaparur Ganesan (Chemical Physics Impact)
This study investigates the anticancer potential of existing anti-viral drugs using a comprehensive suite of computational methods. A dataset of 76 antiviral drugs was prepared and optimized for analysis. Through the application of network pharmacology, gene ontology, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses, this study identified Human Epidermal Growth Factor Receptor 2 (HER2) and Poly [ADP ribose] polymerase 1(PARP-1) as key targets involved in the molecular pathways associated with breast cancer. Protein sequence alignment further revealed conserved and semi-conserved amino acid regions, including residues such as Arginine (ARG), Aspartic acid (ASP), and Phenylalanine (PHE), offering valuable insights into the structural characteristics of the target proteins. Molecular docking studies were performed to evaluate drug-receptor interactions, leading to the selection of promising candidates: Fostemsavir, Efavirenz, Doravirine, and Didanosine for HER2, and Efavirenz, Lopinavir, Fostemsavir, and Elvitegravir for PARP-1. The binding affinities observed were -7.92 Kcal/mol for HER2 and -8.08 Kcal/mol for PARP-1 for Efavirenz, and -8.17 Kcal/mol for HER2 and -7.91 Kcal/mol for PARP-1 for Fostemsavir. Subsequent molecular dynamics simulations, conducted over 200 ns, assessed the stability of these drug-protein complexes. Binding free energy was calculated using Molecular Mechanics/Generalized Born Surface Area (MM-GBSA) methods, reinforcing the stability and efficacy of the selected compounds followed by entropy calculation using Normal mode analysis done for Efavirenz complexes. Results of this study demonstrated that Efavirenz exhibits strong binding and notable potential as HER2 and PARP-1 inhibitors. Efavirenz demonstrated effectiveness against both targets, emphasizing its potential and showcasing drug repurposing as a promising strategy in cancer therapy development.